A EDUCAÇÃO A DISTÂNCIA NO BRASIL LIMITES E POSSIBILIDADES NA IMPLANTAÇÃO DA EAD NO ENSINO SUPERIOR - Rosin, Claudia Aparecida Bueno (2010)
This paper provides an overview of distance education in Brazil, by making a historical contextualization of the subject from the first reported experiments in our country to the current data, which confirm its growth in all levels of education. In this context, we present an analysis on the evolution of Brazilian legislation specific to the Distance Education, as well as the accreditation and implementation processes of this modality in higher education, through the understanding on what the legislation may represent in terms of quality, growth, advancement or delay for Distance Education in Brazil. We also present a concrete experiment of implementation of distance disciplines in two presential undergraduate courses, by examining the issue of the opposition found during the process, and how we overcame the challenges found. The objective of this paper is to inform the reader about the distance learning actual situation in our country, by bringing historical and statistical evidences in order to show how this process can take place in educational practice within the university context, and by analyzing the limits and possibilities of implementation of this modality in higher education.(AU)